Enhancement of Quality of Service (QoS) through Improvement of WCDMA Capacity - Imo, F. U.; Nwabueze, C. A.; Aluhumile, Erukpe P. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Achieving maximum customer satisfaction in the Global System for Mobile Communications (GSM) industry has become increasingly challenging due to heightened awareness of consumer rights, population growth, and economic expansion. A critical factor influencing service delivery is network congestion, which significantly impacts the Quality of Service (QoS), a key performance indicator (KPI) used to assess the efficiency of telecommunication services provided to end users. Core metrics for evaluating QoS include accessibility, voice connection quality, and retainability. While various studies have explored methods to mitigate congestion, interference remains a major constraint on the capacity of Wideband Code Division Multiple Access (WCDMA) systems, especially in regions where population density fluctuates, forming high-demand zones or "hot spots." This study investigates the application of adaptive sectorization as a strategy to reduce co-channel interference. The methodology involves modifying the number of antennas in the base station array, analyzing energy leakage between users, and examining the resulting radiation patterns for three mobile devices to measure inter-user interference. Results indicate that increasing the number of antennas narrows radiation beams and reduces off-diagonal interference levels. The findings demonstrate that adaptive sectorization consistently enhances system capacity, with particularly notable improvements in scenarios where user concentration in hot spots significantly exceeds that in surrounding areas.